Surface Application of Hydrated Lime in Different Crop Systems - Borges, Wander Luis Barbosa; Hipólito, Jorge Luiz; Juliano, Pedro Henrique Gatto [UNESP]; de Souza, Isabela Malaquias Dalto [UNESP]; de Freitas, Rogério Soares; Andreotti, Marcelo [UNESP] (Taylor & Francis, 2022)
To address the problems of acidity in the surface and subsurface layers and improve soil chemical fertility, three methodology of surface application of hydrated lime (HL) (4Ca(OH)2Mg(OH)2) (ensure that calcium (Ca)+2 occupied 70%, 60%, and 50% of cation exchange capacity (CEC) in the 0.0–0.2 m layer) were evaluated in a Typic Hapludalf in conventional pasture system (CPS), no-till system (NTS), and agropastoral system (APS) in Brazil. The results support the following conclusions: (a) the application of HL corrects surface and subsurface acidity and improve the soil chemical fertility: increasing pH and magnesium (Mg)2+ content in the CPS, NTS, and APS in the 0.0–0.2 m and 0.2–0.4 m layers; increasing base saturation (BS) and Mg+2/CEC in the CPS, NTS, and APS in the 0.0–0.2 m layer; increasing Ca+2 content, CEC, and Ca+2/CEC in the NTS and APS in the 0.0–0.2 m layer; reducing total acidity in the CPS, NTS, and APS in the 0.0–0.2 m layer and in the NTS and APS in the 0.2–0.4 m layer; reducing total acidity and increasing Mg+2/CEC in the NTS and APS in the 0.2–0.4 m layer.
Keywords: Agropastoral system; conventional pasture system; no-till system; soil acidity; soil fertility